Математична модель двохфазного потоку процесів зневоднення та гранулювання у псевдозрідженому шарі - Корнієнко, Б. Я. (Видавництво Львівської політехніки, 2011)
The mathematical model of two phase flow of\ dehydration and granulation in fluidized bed. The two phases are considered as continuous and described by the equations of conservation of mass, moments and thermal energy.
Keywords: mathematical model; fluidized bed; granulation; dehydration